Current ulcer care practices among leprosy patients: a systematic review protocol - Thatoju, Pavan Kumar; Nagisetty, Sahaja; Pilaka , Khyathi Reddy (International Journal Of Community Medicine And Public Health, 2025)
Background: Leprosy, or Hansen’s disease, is a chronic infectious condition caused by Mycobacterium leprae or Mycobacterium lepromatosis, predominantly affecting the skin, peripheral nerves, and mucous membranes. Despite being curable, it continues to result in significant morbidity due to delayed diagnosis, stigma, and complications such as chronic trophic ulcers (CTUs). While multiple treatment options exist ranging from debridement and protective footwear to growth factor therapies but their comparative effectiveness remains unclear. Methods: This systematic review and meta-analysis aim to evaluate the effectiveness of various ulcer care practices for individuals affected by leprosy, focusing on outcomes such as healing rates and ulcer recurrence. This systematic review will follow the PRISMA-P 2015 guidelines and is registered in PROSPERO (CRD420251010372). A thorough search will be conducted in databases such as PubMed, Google Scholar, and grey literature from 2005 to 2024. Studies included will be randomized controlled trials (RCTs) and cross-sectional studies that report on ulcer care practices in people affected by leprosy. We will include interventions like wound dressings, debridement, medications, use of footwear, and traditional methods. The quality of the studies will be assessed using standard tools: the Cochrane RoB 2 tool for randomized trials and the Joanna Briggs Institute (JBI) checklist for cross-sectional studies. Data will be analysed using R software. Conclusions: The review will synthesize evidence on the effectiveness of ulcer care interventions in leprosy, guiding clinical decision-making and informing policy to improve healing outcomes and quality of life among affected individuals. Trial Registration: Current control trial registration number is CRD420251010372.